Kidnapped in Yemen : One Woman's Amazing Escape from Captivity - Quin, Mary (Edinburgh Mainstream Publishing, 2006)
When Mary Quin ripped an AK-47 from the hands of a wounded kidnapper and made her escape in the Yemeni desert, she knew her life could never be the same. An exotic vacation had turned into a nightmare. This is a first-hand account of the remarkable woman's unusual story of curiosity, survival and healing.
Include Illustrations, Sources and Appendix.
One Woman's Amazing Escape from Captivity.
Keywords: Yemen (Republic) -- Terrorism -- Kidnapping